Perancangan Game Berbasis Android Untuk Memperkenalkan Adat Melayu Riau - Atan Atan; Zul Indra; Anip Febtriko (LPPM Universitas Abdurrab, 2020)
The difficulty of getting knowledge about local customs especially Riau Malay tradition makes some people around not know much and still apply learning by using books that are still less recorded and too monotonous. Because Malay tradition there is a discussion that requires an explanation of the techniques used in learning and introducing Riau Malay tradition. Riau has many cultures, traditions and customs that are not well known to the younger generation or society in general. Customs and traditions that are believed to be hereditary and are the identity of an area must be maintained and preserved by the younger generation. One of them is Riau's Malay tradition. These customs and traditions need to be published to the public through multimedia, one of which is based on Android. The problem is the lack of knowledge about Riau Malay custom among the community. With this Android-based application, it is hoped that it will be able to preserve Riau Malay tradition more loved by the community.The scope of this study is limited to typical food, traditional clothing, tourism This type of research is descriptive research, using the method of field surveys and interviews with direct sources. This research aims to preserve the tradition of Malay Malay so that it does not become extinct and can be enjoyed by subsequent generations.